Transfer of an Esterase-resistant receptor analog to the surface of iInfluenza C virions results in reduced infectivity due to aggregate formation - Höfling, Katja; Brossmer, Reinhard; Klenk, Hans-Dieter; Herrler, Georg (Virology, 1996)
A synthetic sialic acid,N-acetyl-9-thioacetamidoneuraminic acid (9-ThioAcNeu5Ac), is recognized by influenza C virus as a receptor determinant but—in contrast to the natural receptor determinant,N-acetyl-9-O-acetylneuraminic acid—is resistant to inactivation by the viral acetylesterase. This sialic acid analog was used to analyze the importance of the receptor-destroying enzyme of influenza C virus in keeping the viral surface free of receptor determinants. Enzymatic transfer of 9-ThioAcNeu5Ac to the surface of influenza C virions resulted in the loss of the hemagglutinating activity. The ability to agglutinate erythrocytes was restored when the synthetic sialic acid was released from the viral surface by neuraminidase treatment. Infectivity of influenza C virus containing surface-bound 9-ThioAcNeu5Ac was reduced about 20-fold. Sedimentation analysis as well as electron microscopy indicated that virions resialylated with the esterase-resistant sialic acid analog formed virus aggregates. These results indicate that the receptor-destroying enzyme of influenza C virus is required to avoid the presence of receptor determinants on the virion surface and thus to prevent aggregate formation and a reduction of the infectious titer.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 27.06.2024